Complications after dental rehabilitation under general anesthesia in Isfahan during February to May 2016 - Maryam Ghafournia; Alireza Eshghi; Hamid Mosleh; Pedram Iranmanesh (Wolters Kluwer Medknow Publications, 2021)
Background: Children undergoing dental rehabilitations by general anesthesia (GA) commonly experience postoperative symptoms such as pain, fever, sore throat, and sleepiness. The aim of the present study was to investigate the specific complications of pediatric dental GA procedure. Materials and Methods: In this observational study sample included 72 children attending GA for dental treatment at the School of Dentistry, Isfahan University of Medical Sciences. Children with American Society of Anesthesiologists physical status I and without any communication or mental health problems were included. GA protocol was standardized. A number of complications were recorded by parents via filling a questionnaire for 2 days postoperatively. Data were analyzed using SPSS statistical software by Wilcoxon and Chi-squared test. P < 0.05 considered as significant level. Results: The most postoperative nonpsychological complications were dental pain (59.7 and 47.2% on days 1 and 2, respectively), followed by inability to eat normal (55.6 and 41.7% on days 1 and 2, respectively). All the patients' nonpsychological complaints had significantly decreased from day one to day two (P < 0.05). The most postoperative psychological complications were Attachments to parents (70.8 and 65.2% on days 1 and 2, respectively) followed by excessive crying (56.9 and 45.8% on days 1 and 2, respectively). All psychological complaints reduced by day two nonsignificantly except excessive crying which decreased significantly after 48 h (P = 0.004). Conclusion: The most postoperative complications after dental rehabilitation under GA were attachments to parents, dental pain, and inability to eat normal and excessive crying, respectively.